PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH BANK BRI SYARIAH DI SAMARINDA - Apriadi Pratama; . Rusmilawati; Ardi Parminto (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2013)
This study aims to determine the effect of service quality consisting of Reliability (X1), Responsiveness (X2), Assurance (X3), Empathy (X4), and Tangible (X5) customer satisfaction (Y1) and customer loyalty (Y2) at Bank BRI Sharia in Samarinda. T test results are known effects of service quality on customer satisfaction (Y1). Variable Reliability (X1) significant because the level (sig <0.05), namely (0.000 <0.05). Variable Responsiveness (X2) is significant (0.036 <0.05). Variable Assurance (X3) is significant (0.000 <0.05). Empathy variable (X4) is significant (0.001 <0.05). Tangible variable (X5) had no significant effect due to the level (sig> 0.05), namely (0.627> 0.05).